NEUROLOGICAL DISORDERS IN PATIENTS WITH HYPERTENSION AND THEIR CORRECTION - N. V. Vakhnina; O. V. Milovanova (Неврология, нейропсихиатрия, психосоматика, 2016)
Neurological disorders in hypertensive patients can be caused by both brain injury and concomitant diseases. The elucidation of the causes of neurological disorders and their effective treatment contribute to hypertensive patients’ better adherence to long-term antihypertensive therapy, which normalizes blood pressure (BP) and reduces the risk of cerebral complications Objective: to study of the causes of neurological disorders in hypertensive patients and the efficiency of their correction using a new dispersible vinpocetine formulation (Cavinton® Comforte) in combined therapy.Patients and methods. A total of 80 patients (men (20%) and women (80%); mean age 63±12.3  years) with neurological complaints in the presence of hypertension were examined. All the patients were diagnosed with dyscirculatory encephalopathy or chronic brain ischemia, whether they had vascular cognitive impairment. The examination of patients revealed that the neurological complaints were mainly due to concomitant diseases, such as migraine (12%), tension-type headache (66%), and the latter concurrent with migraine (4%).Results and  discussion. The  effective treatment of concomitant diseases in  combination with antihypertensive therapy contributed to normalization of BP and regression of complaints. The most pronounced effect was noted in 40 patients whose combination therapy included Vinpocetine (Cavinton® Comforte) 10 mg thrice daily.Conclusion. The therapy resulted in the less severity of both the symptoms of cerebrovascular disease (vascular cognitive impairment) and comorbid neurological disorders (headache, dizziness, etc.).